Relatório de Estágio Profissionalizante realizado na equipa de Sub-17 de futebol masculino do Lusitânia de Lourosa Futebol Clube, Época DesporFva 2023/2024 - Caio Cesar Junior Gomes da Silva (2024)
This report aims to document the experiences during the Second Cycle Professional Internship in High-Performance Sports Training at the Faculty of Sport of the University of Porto (FADEUP). The internship was carried out at Lusitânia de Lourosa Futebol Clube, with the Under-17 team, during the 2023/2024 season, a team that competed in the national second division for youth teams. This report aims to reflect on the experiences encountered during the sports season in question. It presents how my internship took place and includes reflections on various topics that significantly contributed to my personal and professional development. It also outlines the methodological approach we used, along with all the training processes and ideas to perform at our best. Thus, in addition to reflections on various topics that were crucial for the outcome of our Under-17 sports season, I also highlight the importance of this internship in achieving my success as the head coach of the Under-18 team. The report begins with a summary of my background, initial expectations, and personal goals I set out to achieve. Then, I provide context about the club and the location where the internship took place, along with a description of the technical staff members I worked with and my role as a trainee coach. I then describe the objectives set by the technical team, particularly those related to training, preparation, and performance. I also discuss the game model presented by the two coaches, mentioning the systems and principles for each phase of the game. In this chapter, I also refer to the weekly pattern and training units. In the last part of the report, I reflect on key moments, especially during the preseason, the first phase of the championship, and the second phase of the championship. I also discuss important moments for reflection and some experiences throughout the internship. This internship was very important for my development as a football coach, as it was the season in which I evolved the most as a coach, experiencing unique situations that greatly contributed to my formative process.